AN ANALYSIS OF CONSUMER VIEWS AND SATISFACTION WITH ONLINE FOOD DELIVERY SERVICES - Parul Sharma and Dr. Monika Khatri (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Online food ordering is a method that uses mobile apps or websites to make it easier for local restaurants and other food companies to deliver or takeout food. This systematic approach to food delivery is becoming increasingly common, particularly with younger people using smartphone applications to order food. Thanks to this, customers can make orders with fewer mistakes and have meals delivered right to their door. India's food delivery business has a long history. It started in the 1890s when Indian dabbawallas delivered meals in crowded cities like Mumbai. Originally, they used local railroads for this service, but now they employ mail, SMS, and internet platforms. The food delivery industry is predicted to develop at a high pace of thirty per cent per year and reach a value of around 21 billion by 2026. The COVID-19 epidemic has further expedited this expansion. As a result, more delivery-focused firms are looking for ways to grow their offerings. Zomato and Swiggy are the two leading companies in India's online meal delivery app industry and other established companies. This study aims to investigate the elements that impact consumers' opinions on online food delivery apps, how consumers in perceive these apps, and gauge how satisfied customers are with online meal ordering services. The study uses a descriptive research design and gathers information from a sample of one hundred respondents using structured questionnaires. The study's conclusion highlights the need to pay close attention to customer satisfaction and states that it is a critical component of the meal delivery business.